2017
DOI: 10.14202/vetworld.2017.786-789
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in lipid profile in neonatal calves affected by diarrhea

Abstract: Aim:The aim of this study was to determine the alterations in the lipid profile, plasma alkaline phosphatase (ALP) activity, total and direct bilirubin levels of neonatal calves with diarrhea.Materials and Methods:A total of 25 calves with diarrhea as experimental group and 10 healthy calves as control group, 1-30 days old, were enrolled in the study. Blood samples were collected from jugular vein in tubes with anticoagulant agent to evaluate the concentration of triglycerides, total cholesterol, high-density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…The latter increases chol and TAG levels (Cavestany et al, 2005). The concentrations of glu, chol, and TAG can be altered by infection or diet (Bozukluhan et al, 2017). This observation is consistent with our results because the incidence of diarrhea was higher in the CR group than in the TRT group (10 vs. 6 diarrhea cases, respectively).…”
Section: Discussionsupporting
confidence: 91%
“…The latter increases chol and TAG levels (Cavestany et al, 2005). The concentrations of glu, chol, and TAG can be altered by infection or diet (Bozukluhan et al, 2017). This observation is consistent with our results because the incidence of diarrhea was higher in the CR group than in the TRT group (10 vs. 6 diarrhea cases, respectively).…”
Section: Discussionsupporting
confidence: 91%
“…This result may be because of muscle damage in bedridden calves with sepsis. Studies have reported increased serum ALT, AST, GGT, and ALP concentrations in neonatal calves with diarrhea symptoms (Başer and Civelek, 2013 ; Bozukluhan et al 2017 ; Naseri, 2017 ). Similarly, this study found higher concentrations of serum ALT, AST, GG, and ALP in calves with sepsis than in healthy ones.…”
Section: Discussionmentioning
confidence: 99%
“…S2). Overall, these results suggest that total cholesterol and γ-GT may be useful as blood biomarkers to monitor FMT e cacy [30,31].…”
Section: Resultsmentioning
confidence: 96%